MONEY FLEXIBILITY AND OPTIMAL CONSUMPTION-LEISURE CHOICE UNDER PRICE DISPERSION - MALAKHOV, Sergey (Theoretical and Practical Research in Economic Fields; Vol 4 No 1 (2013): TPREF, Volume IV, Issue 1(7), Summer 2013, 2013)
The synthesis of G.Sigler’s rule of the optimal search with the classical individual labor supply model can incorporate the satisficing decision procedure in the neoclassical framework. Many psychological anomalies and puzzles like the paradox of little pre-purchase search for big-ticket items and the effect of sunk costs sensitivity get the purely economic rationale. This synthesis also enlarges the understanding of the phenomenon of money flexibility under price dispersion. The specific constraints of the search model establish the correspondence between elasticity of the marginal utility of labor income with regard to price dispersion, wage rates, and the propensity to search. The money flexibility under price dispersion discovers specific features of Veblen effect. The marginal utility of labor income becomes negative, when the smart shopping of luxuries results in price reductions, which are greater than the wage rate. The marginal utility of luxuries also becomes negative. And the total consumption-leisure utility is increasing only due to the increase in leisure time. The paper argues that the same mechanism underlies the phenomenon of money illusion due to the relatively excess money balances.